Physical Therapist Practice in the Emergency Department Observation Unit: Descriptive Study. Issue 2 (1st February 2015) - Plummer, Laura; Sridhar, Sowmya; Beninato, Marianne; Parlman, Kristin
Abstract : Background: An upward trend in the number of hospital emergency department (ED) visits frequently results in ED overcrowding. The concept of the emergency department observation unit (EDOU) was introduced to allow patients to transfer out of the ED and remain under observation for up to 24 hours before making a decision regarding the appropriate disposition. No study has yet been completed to describe physical therapist practice in the EDOU. Objective: The objectives of this study were: (1) to describe patient demographics, physical therapist management and utilization, and discharge dispositions of patients receiving physical therapy in the EDOU and (2) to describe these variables according to the most frequently occurring diagnostic groups. Design: This was a descriptive study of patients who received physical therapist services in the EDOU of Massachusetts General Hospital during the months of March, May, and August 2010. Methods: Data from 151 medical records of patients who received physical therapist services in the EDOU were extracted. Variables consisted of patient characteristics, medical and physical therapist diagnoses, and physical therapist management and utilization derived from billing data. Descriptive statistics were used to analyze data. Results: The leading EDOU medical diagnoses of individuals receiving physical therapist services included people with falls without fracture (n=30), back pain (n=27), falls with fracture (n=22), and dizziness (n=22). There were significant differences in discharge disposition, age, and total physical therapy time among groups. Limitations: This was a retrospective study, so there was no ability to control how data were recorded. Conclusions: This study provides information on common patient groups seen in the EDOU, physical therapist service utilization, and discharge disposition that may guide facilities in anticipated staffing needs associated with providing physical therapist services in the EDOU.